ANALISIS PENGARUH KEPEMILIKAN BANK, KONSENTRASI KEPEMILIKAN, BOPO, LDR, BANK SIZE, DAN CAR TERHADAP NON PERFORMING LOANS (Studi Empiris pada Bank Umum Konvensional di Bursa Efek Indonesia Periode 2009-2013) - Putri Gantika, Fauziah; Demi Pangestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2015)
This Research aims to analyze the influence of bank ownership, ownership concentration, operating cost to operating income ratio (BOPO), Loan to Deposit Ratio (LDR), bank size, and Capital Adequacy Ratio (CAR) to credit risk that measured by NPL. Case Study on conventional commercial banks in Indonesia Stock Exchange in period 2009-2013.Research population used is conventional commercial banks in Indonesia in period 2009-2013. Taken samples of the all-purpose 24 banks by using purposive sampling method. The data used in this study were obtained from the Banking Annual Report 2009-2013. Analysis technique used is Ordinary Least Square Regression (OLS), statistical t-test and classic assumption test that includes a test of normality test, multicollinearity test, heteroskedastisitas test, autocorrelation test.The resultÂ shows that bank ownership has significant positive association with NPL, concentration ownership has insignificant negative association with NPL, and Loan to Deposit Ratio has insignificant positive association with NPL. Operating cost to operating income ratio, bank size, and Capital Adequacy Ratio have significant negative association with NPL. The results of regression estimation show the ability of model prediction is 21,6% while the remaining 78,4% influenced by other factors outside the model.